Pengaruh Kelengkapan Produk, Tata Letak Toko, dan Fasilitas Terhadap Minat Beli Ulang Konsumen Swalayan Purnama Di Kabupaten Bantul - Dewi Manda Sari; Murti Sumarni; Anindita Imam Basri (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
The population used in this study were all consumers who shopped at the Purnama supermarket. The sample in this study was 80 respondents and used a non-probability sampling technique. Data analysis using SPSS 20. The results showed that partially the completeness of the product had a positive and significant effect on repurchase intention. Store layout has a positive and significant effect on repurchase intention. have a positive and significant effect on repurchase intention. Simultaneously product completeness, store layout, and facilities have a positive and significant effect on repurchase intention. The effect of product completeness, store layout, and facilities on the purchase intention of Purnama supermarket consumers in Bantul Regency is indicated by the Adjusted R2 value of 96.6%.